Small-scale Capture Fisheries : A Global Overview with Emphasis on Developing Countries - Food and Agriculture Organization of the United Nations (World Bank, Washington, DC, 2014)
Fisheries contribute greatly to the well-being of many millions of people. The sector generates employment and economic values that are important to individuals, communities and national economies. However, the world's fishery resources are not infinite, and appropriate conservation must be employed for ensuring sustainable livelihood through fisheries in the future as well. The Big Numbers Project, a collaborative effort by the Food and Agriculture Organization (FAO), WorldFish Center and World Bank, addresses the lack of accurate and accessible disaggregated information on small and large-scale fisheries, in inland and marine waters, currently experienced in the international fisheries arena. This is a preliminary report of the project, giving a summary of the results of case studies carried out in a selected number of countries and providing a first analysis of the differences between marine and inland small and large-scale fisheries in developing countries.